2009
DOI: 10.1093/carcin/bgp058
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to esophageal cancer: the role of the nucleotide excision repair pathway

Abstract: In this case-control study with 387 White esophageal patients and 462 White controls matched to cases by age and sex, we evaluated the associations between 13 potential functional polymorphisms in eight major nucleotide excision repair (NER) genes and esophageal cancer risk. In individual single nucleotide polymorphism analysis, after adjustment for multiple comparisons, the heterozygous GT genotype of the ERCC1 3' untranslated region (UTR) was associated with an increased risk, whereas the homozygous variant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 34 publications
3
35
1
Order By: Relevance
“…The additional functions of XPG are evident by the presence of structural motifis that are common with proteins involved in repair-recombination and cell cycle regulation (Klungland et al, 1999). It is reported that polymorphisms in XPG are associated with various cancers, such as colorectal cancer, esophageal cancer and lung cancer as well as bladder cancer (Chang et al, 2008;Pan et al, 2009;Rouissi et al, 2011;Liu et al, 2012). However, there was only one study conducted in Chinese population about the association between XPG and gastric cancer risk .…”
Section: Introductionmentioning
confidence: 99%
“…The additional functions of XPG are evident by the presence of structural motifis that are common with proteins involved in repair-recombination and cell cycle regulation (Klungland et al, 1999). It is reported that polymorphisms in XPG are associated with various cancers, such as colorectal cancer, esophageal cancer and lung cancer as well as bladder cancer (Chang et al, 2008;Pan et al, 2009;Rouissi et al, 2011;Liu et al, 2012). However, there was only one study conducted in Chinese population about the association between XPG and gastric cancer risk .…”
Section: Introductionmentioning
confidence: 99%
“…5 To date, a number of molecular epidemiological studies have been done to evaluate the association between XPA À4G>A polymorphism and different types of cancer risk in diverse populations. The tumor types included lung cancer, 6,13,22,24,[29][30][31][32][33][34] gastric cancer, 7,17 colorectal cancer, 8,12,23 squamous cell carcinoma of the head and neck, 8,10 basal and squamous cell carcinomas of the skin (BCC and SCC), 20,27 breast cancer, 8,18,26 esophageal cancer, 11,14,15 and so on. However, the results were inconsistent or even contradictory.…”
mentioning
confidence: 99%
“…1. Two cancer types were included in the studies by Pan and Ye; therefore, there were 21 case-control studies in this meta-analysis (23,28). As shown in Table 1, there were 14 case-control studies, including 3,457 cancer cases and 4,855 controls, of the XPD Lys751Gln polymorphism and ESCC risk and seven studies, including 1,726 cases and 3,396 controls, of the XPD Lys751Gln polymorphism and EADC risk.…”
Section: Study Characteristics and Resultsmentioning
confidence: 99%